2020
DOI: 10.1161/strokeaha.120.030574
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Ischemic Stroke due to Large Vessel Occlusion With COVID-19

Abstract: Background and Purpose: Higher rates of strokes have been observed in patients with coronavirus disease 2019 (COVID-19), but data regarding the outcomes of COVID-19 patients suffering from acute ischemic stroke due to large vessel occlusion (LVO) are lacking. We report our initial experience in the treatment of acute ischemic stroke with LVO in patients with COVID-19. Methods: All consecutive patients with COVID-19 with acute ischemic stroke due to LVO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(247 citation statements)
references
References 12 publications
22
216
1
5
Order By: Relevance
“…To our knowledge, this is the first study that compares COVID-19 patients to non-COVID-19 patients within a prospectively collected stroke database. Similar to previous case reports and case-controlled studies, from USA ( 10 ), Iran ( 26 ), Dubai ( 27 ), France ( 28 ) and China ( 8 ), a third of our COVID-19 positive patients had severe disease, required ICU admissions, stayed longer in hospital and had fewer subjects with good outcome. These patients likely represent a subset of stroke patients in whom the viral infection likely contributed to a prothrombotic state resulting in vascular occlusions and large strokes.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, this is the first study that compares COVID-19 patients to non-COVID-19 patients within a prospectively collected stroke database. Similar to previous case reports and case-controlled studies, from USA ( 10 ), Iran ( 26 ), Dubai ( 27 ), France ( 28 ) and China ( 8 ), a third of our COVID-19 positive patients had severe disease, required ICU admissions, stayed longer in hospital and had fewer subjects with good outcome. These patients likely represent a subset of stroke patients in whom the viral infection likely contributed to a prothrombotic state resulting in vascular occlusions and large strokes.…”
Section: Discussionsupporting
confidence: 87%
“…A total sample of 8,771 participants was included in the systematic review. These studies were conducted in many countries worldwide including in China ( 13 , 40 , 43 ), France ( 37 , 39 , 48 , 50 ), India ( 42 ), Iran ( 51 ), Italy ( 32 , 33 , 46 ), the Netherlands ( 34 ), Philippines ( 52 ), Spain ( 44 , 53 ), Turkey ( 58 ), UK ( 41 , 55 ), and the USA ( 21 , 35 , 36 , 45 , 47 , 49 , 54 , 56 , 57 ). Out of 27 studies, eight studies were of retrospective cohort study design, 11 were case series, and nine were case reports.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of stroke were almost equal for LVO (47 stroke cases in 10 studies) and non-LVO (42 cases in 10 studies). Location of LVOs involved were M1 vessels ( 21 , 37 , 41 , 42 , 44 , 45 , 47 , 53 , 54 ), M2 vessel ( 41 , 42 , 44 , 45 , 47 , 53 ), internal carotid ( 21 , 37 , 42 , 45 , 47 , 53 ), multiteritorial ( 37 , 47 ), posterior cerebral ( 41 , 45 ), basilar ( 37 ), ACA ( 21 , 53 ), and the vertebral artery ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sinai Hospital in New York, after thrombectomy, most of the large arteries with occlusive thrombus appeared normal (M. Alberts, personal communication, May 28, 2020). Escalard et al [27] reported that among 10 patients with stroke and COVID-19, 5 had large artery occlusions in multiple vascular territories. This suggests that large artery occlusion in COVID-19 may be mainly cardioembolic/paradoxical.…”
Section: Hypercoagulable Statementioning
confidence: 99%